Da proposta à concretização: o fim do departamento na reforma administrativa da Universidade Federal de Alagoas - UFAL - Oliveira, Jorge Eduardo de (2017)
This PhD thesis aims to contribute to the history of Universidade Federal de Alagoas- UFAL and to the education of Alagoas, bringing the discussion about Power and Rationalization in educational organizations. It is limited to the elaboration of the administrative order of UFAL approved by the Ministry of Education in 2003, analyzing the discussions, actions and documents, as well as the actors action (individual and group), who advocated the end of the teaching department of the organization Centro -Department in the creation of academic units. The historical period was limited from 1987 to 2001, during which discussions were held at the University Council, a university congress was held (1997) and a proposal for administrative order was drawn up, as well as the systematization of contributions. We use theoretical references related to the discussion about Rationality and Bureaucracy, with references such as Max Weber (1982, 1994), Julien Freund (1966) and Roderick Martin (1978), necessary to understand the orientation of action of subjects and groups, strategies And action logic in the implementation of a specific political-administrative project. We use the Weberian methodology of the "Ideal Type", which was constructed having as categories "instrumentally rational action", "value-rational action" and "rational Grounds (Bureaucracy). We divide the text into four parts, as established: (1) Introduction (2) Methodology, (3) Theoretical References, (4) Theoretical References and University, (5) Analysis and (6) Final Considerations, in which we verify the role played By central management, and by a group of teachers, in the process of construction and approval of a proposal for adminstrative order that extinguished the administrative structure based on Centers and Departments, as well as the Department of Education itself, rearranging power relations in decision-making processes, strengthening The role of “Colegiados de Curso” and members of courses in their relationship in the upper management spaces of the organization.